Contre toute attente. L'attention dans l'expérience de l'œuvre d'art - Olcèse, Rodolphe (Labyrinth, 2020)
Against all expectations. The phenomenon of attention in aesthetic experience This paper aims to show how aesthetic experience, by the type of attention it requires, can lead us to consider sensitivity as a way to take care of the visible. Based on a reflection about the concept of repetition developed by Sören Kierkegaard, it is shown how attention is at the same time a manner to concern for oneself and to concern for the sensitive environment. The main thesis of this article is that artistic creation can be considered as a privileged path to experiment in how far the expectation influences our perception of the sensitive. By inviting us to embrace a certain kind of presence, art works can as well be considered as an outstanding way of access to reality